1999
DOI: 10.1016/s0167-8760(99)00083-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between auditory ERP and neuropsychological assessments in schizophrenia☆

Abstract: To clarify the cognitive significance of event-related potential (ERP) abnormalities in schizophrenia, we examined the relationships of amplitudes and latencies of ERP components with performance on neuropsyhological tests in schizophrenic patients. Twenty patients underwent the Trail Making B Test (TM-B), which is sensitive to frontal lobe dysfunction, and the logical memory, verbal paired-association, and visual reproduction subtests of the Wechsler Memory Scale (WMS), which are sensitive to temporal lobe dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
2
11
1
Order By: Relevance
“…Poor verbal memory and temporal P300 amplitude differences were correlated in our EIPS sample, suggesting that lateralized structural abnormalities may underlie both these deficits. Two other studies with schizophrenia patients showed the same association between left temporal P300 amplitude and verbal memory (Nagasawa et al, 1999;Kim et al, 2003).…”
Section: Is Left Temporoparietal P300 Amplitude a Vulnerability Marker?supporting
confidence: 54%
“…Poor verbal memory and temporal P300 amplitude differences were correlated in our EIPS sample, suggesting that lateralized structural abnormalities may underlie both these deficits. Two other studies with schizophrenia patients showed the same association between left temporal P300 amplitude and verbal memory (Nagasawa et al, 1999;Kim et al, 2003).…”
Section: Is Left Temporoparietal P300 Amplitude a Vulnerability Marker?supporting
confidence: 54%
“…For example, patients with schizophrenia exhibit reductions in gray matter volume in the frontal and temporoparietal areas [51] and an association between reduced P300 amplitudes and reduced volumes of the left superior temporal gyrus [52] and parietal areas [53] has been reported. Negative correlations have also been observed between P300 amplitudes and performance on verbal memory tests [12] [16]. However, in the present study, the schizotypal-trait and control groups did not differ in terms of performance on the verbal and nonverbal memory tests.…”
Section: Discussioncontrasting
confidence: 66%
“…An examination of the relationship between P300 abnormalities and neuropsychological performance may contribute to a better understanding of the clinical significance associated with reduced P300 amplitudes. Patients with schizophrenia exhibit significant negative associations between P300 amplitudes and performance on the verbal paired-association [16] and visual memory [17] tests of the Wechsler Memory Scale. Additionally, P300 amplitudes and verbal memory performance on the Luria-Nebraska Verbal Learning Test are negatively correlated [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the P300 has been shown to vary as a function of many factors, among others attention and vigilance, P300 waves from subjects who did not perform the P300 task properly behaviorally (e.g., number of correct responses, number of correctly counted deviant stimuli) should not be considered valid measures. On the other hand, Strick et al (1991) suggest it is very specifi c to schizophrenia and is not positive in other paranoid or delusional diseases; some studies fi nd strong correlation between P300 alterations and abnormal responses to neuropsychological tests (Nagasawa et al 1999).…”
Section: Electroencephalography (Eeg) and Magnetoencephalography (Meg)mentioning
confidence: 99%